2004
DOI: 10.1084/jem.20041545
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin-11 Provides Specific Cellular Adhesion between Fibroblast-like Synoviocytes

Abstract: Cadherins are integral membrane proteins expressed in tissue-restricted patterns that mediate homophilic intercellular adhesion. During development, they orchestrate tissue morphogenesis and, in the adult, they determine tissue integrity and architecture. The synovial lining is a condensation of fibroblast-like synoviocytes (FLS) and macrophages one to three cells thick. These cells are embedded within the extracellular matrix, but the structure is neither an epithelium nor an endothelium. Previously, the basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
114
0
1

Year Published

2008
2008
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 151 publications
(124 citation statements)
references
References 26 publications
9
114
0
1
Order By: Relevance
“…After the third passage, cells appeared fibroblast-like. Fluorescence-activated cell sorting (FACS) confirmed that the cells were negative for F4/80 and CD45 and positive for vascular cell adhesion molecule 1 (VCAM-1), suggesting that the cultures were FLS as previously described (4).…”
Section: Methodssupporting
confidence: 68%
See 2 more Smart Citations
“…After the third passage, cells appeared fibroblast-like. Fluorescence-activated cell sorting (FACS) confirmed that the cells were negative for F4/80 and CD45 and positive for vascular cell adhesion molecule 1 (VCAM-1), suggesting that the cultures were FLS as previously described (4).…”
Section: Methodssupporting
confidence: 68%
“…Cadherin 11 has recently been identified on human and murine FLS and has been proposed to be a key mediator of synovial lining architecture and synovial inflammation (4)(5)(6). In the present study, we demonstrated that in addition to cadherin 11, FLS express a second mesenchymal cadherin, N-cadherin, but do not express the epithelial cadherin, E-cadherin.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…4A). Cadherin-11 is used by FLS in homotypic adhesive interactions, is expressed by synovial lining FLS, and is important for the overall morphology and development of the synovial lining (27). Monochromatic staining of B7-H3 or cadherin-11 showed almost identical patterns of expression.…”
Section: B7-h3 Is Broadly Expressed In Ra Synoviummentioning
confidence: 86%
“…The homophilic interaction of FLS in synovial tissue was recently demonstrated to be mediated by cadherin 11, a classic cadherin that is primarily expressed by mesenchymal cells (19). Cadherins are a large family of transmembrane homodimeric proteins that are physically linked to the actin cytoskeleton via their cytoplasmic domain.…”
mentioning
confidence: 99%